Genesis of lateral differences of swimmers - Witt, M.; Hermsdorf, M. (Revista Portuguesa de Ciências do Desporto, 2006)
INTRODUCTION In swimming evenly distributed movements are performed by the limbs. Nevertheless differences in the motion of the left and right body side are to be observed frequently. These effects are strongly related with breathing and lead to necessary correction movements, without a propulsion effect. A goal of the investigation was to quantify the energetic causes of these side differences.